FPGA-based real-time data processing for accelerating reconstruction at LHCb. (1st April 2022) - Lazzari, F.; Baldini, W.; Bassi, G.; Contu, A.; Dorigo, M.; Fantechi, R.; Giambastiani, L.; Morello, M.J.; Punzi, G.; Sticchi, M.; Tuci, G.; ,
Abstract: In run-3, beginning in 2022, the LHCb software trigger will start reconstructing events at the LHC average crossing rate of 30 MHz. Within the upgraded DAQ system, LHCb established a testbed for new heterogeneous computing solutions for real-time event reconstruction, in view of future runs at even higher luminosities. One such solution is a highly-parallelized custom tracking processor ("Artificial Retina"), implemented in state of the art FPGA devices connected by fast serial links. We describe the status of a realistic prototype for the reconstruction of pixel tracking detectors that will run on real data during run-3.